Pengaruh Digital Payment Terhadap Prilaku Konsumtif Masyarakat - Kintan Rahayu; Dedi Mulyadi (Yayasan Daarul Huda Kruengmane, 2023)
This study aims to investigate the effect of digital payments on people's consumptive behavior. In the growing digital era, digital payments have become one of the main ways to make transactions online. This phenomenon produces a significant impact on people's consumptive behavior. The research method used is a survey through questionnaires distributed to respondents who are digital payment users. The research sample consisted of residential residents, college students, and students in Karawang, with a sufficient number of respondents for accurate analysis. The data obtained were analyzed using descriptive statistical methods and regression analysis. The results of the study show that the effect of digital payments is quite influential on people's consumptive behavior by 68.6% and the remaining 47.1% is influenced by other variables not included in the study. This research found that the more often individuals use digital payments, the more vulnerable they are to excessive consumptive behavior. Factors such as convenience, speed and convenience in using digital payments also contribute to the intensity of use and increased consumer behavior.